PENGARUH KONSULTASI PERPAJAKAN DAN PENGAWASAN PERPAJAKAN OLEH ACCOUNT REPRESENTATIF TERHADAP KEPATUHAN WAJIB PAJAK DI DJP KPP PRATAMA MAKASSAR SELATAN - Subhan Subhan; Edy Susanto (Universitas Muhammadiyah Makassar, 2020)
This research was conducted with the aim of: (1) To analyze the effect of consultation by the Account Representative on taxpayer compliance; and (2) To analyze the effect of supervision by the Account Representative on taxpayer compliance at the Makassar South KPP. This study uses primary data through a survey of 100 corporate and individual taxpayer respondents. The analysis used in this study is multiple regression analysis, which is a regression model to analyze more than one independent variable. The results of this study are (1) Based on simultaneous tests, consultations provided by Account Representatives and supervision provided by Account Representatives have a positive and significant effect on taxpayer compliance, (2) Based on partial tests, tax consulting variables provided by Account Representatives, and supervision provided by the Account Representative has a significant effect on taxpayer compliance.